RANCANGAN PASOK ENERGI DENGAN SEL SURYA UNTUK REAKTOR PENGHASIL BIOETANOL BERBASIS MIKROALGA - , SITI KOIROMAH, Rachmawan Budiarto, S. T, M. T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Today, the world population is increase at an alarming rate, so does the demand for liquid fuels in the transportation sector. The using of biofuels as source of alternative energy has been done in developing and developed countries. Likewise, Indonesian government which publishes the policy for blending premium fuel amount of 10% through Presidential Decree (Perpres)No. 5/2006 andInpres No. 1/2006. The reason of selecting microalgae as the source of bio - ethanolâs material because it has a rapid growth rate, do not compete with food plant and do not contend with agricultural land for cultivation in the sea. Design of this bioethanol productionreactor use three main processes, there are acid hydrolysis, fermentation and purification (distillation and dehydration). Energy calculating is the loaded energy which required producing bioethanol with100 liters capacity each time production for 4 days. The needed energy is a daily load component of operating reactors but does not include the heating load because the heating load in this system which use natural gas. So that, the load requirement which supplied by solar system is 36 kWh, the chosen of solar cell system is the off â grid system, because the production process runs continuously, so it takes an independent source.In addition to, the offâ gridsystem has more stable capacity. Based on the installed modules is required Panasonic module HIT - VBHN240SA06 type 35 pieces , 1 Fronius IG Plus V inverter , 1 piece Charge Controller Xantrex XW - MPPT80 600 and Concorde Sun Xtender battery 84 deep cycle battery 255Ah PVX - 2580L